The degree of Sciences Teachers Practice of Formative evaluation methods from subjectivity evaluation point of view A field study on a sample of science Teachers for fourth grade in the first section - أيوب, رنيم (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
The research aims to monitor the degree of sciences teachers practice fourth grade of formative evaluation methods from their point of the view in the light of developed curricula. The researcher has constructed a questionnaire that included Formative evaluation methods used in evaluating sciences subject. As well, asking one question for the aim of knowing the difficulties and obstacles limiting the degree of sciences teachers practice of formative evaluation methods. The research conducted a set of results indicating the existence of a high level practice of Formative evaluation methods by science teachers of the fourth grade concerning class discussion, exercises, worksheets and follow-up, learner performance observation, self-evaluation. The results have also shown that there are statistically significant differences between the research medium degree members to that of the method to the number of experience in favor of teachers with more than ten years of experience, the results have also shown that there are statistically significant differences between the research medium degree members to that of the method to the scientific qualification in favor of teachers with higher educational qualifications.